Closed Reduction and Casting for a Gartland Type IIB Supracondylar Humerus Fracture in a Child: A Case Report - Samy Elharoun, Mohamed; Saber Eldesoky, Khaled; Alshwekany, Saeed (Journal of Neonatal Surgery, 2025)
The most prevalent kind of elbow fracture that occurs among kids is a supracondylar fracture of the humerus. Type IIB fractures, characterized by posterior displacement with translation/rotation but intact cortical contact, remain controversial in management. This case report describes a seven-year-old male who had a Gartland Type IIB supracondylar fracture of the humerus following a fall onto an outstretched hand and who presented with visible deformity and pain. X-rays confirmed displacement with intact cortical contact. The closed reduction technique achieved satisfactory realignment of the fracture fragments, and application of a high above-elbow cast maintained the reduction, verified by post-reduction X-rays. Weekly radiographic monitoring ensured proper positioning during the healing process. The patient achieved fracture union within 4 weeks; cast removal revealed full elbow range of motion, with no residual deformity or functional limitations at the one-year follow-up. This case aligns with findings that nonoperative treatment, when closely monitored, can yield excellent functional and radiographic results. This case highlighted the importance of appropriate fracture classification, prompt treatment, and regular follow-up to ensure optimal functional recovery in pediatric supracondylar fractures.